A centrifugal microfluidic device with integrated gold leaf electrodes for the electrophoretic separation of DNA. Issue 23 (21st October 2016) - Thompson, Brandon L.; Birch, Christopher; Nelson, Daniel A.; Li, Jingyi; DuVall, Jacquelyn A.; Le Roux, Delphine; Tsuei, An-Chi; Mills, Daniel L.; Root, Brian E.; Landers, James P.
Abstract : A centrifugal microdevice with integrated gold leaf electrodes capable of high resolution electrophoretic separation of DNA fragments. Abstract : Current conventional methods utilized for forensic DNA analysis are time consuming and labor-intensive requiring large and expensive equipment and instrumentation. While more portable Rapid DNA systems have been developed, introducing them to a working laboratory still necessitates a high cost of initiation followed by the recurrent cost of the devices. This has highlighted the need for an inexpensive, rapid and portable DNA analysis tool for human identification in a forensic setting. In order for an integrated DNA analysis system such as this to be realized, device operations must always be concluded by a rapid separation of short-tandem repeat (STR) DNA fragments. Contributing to this, we report the development of a unique, multi-level, centrifugal microdevice that can perform both reagent loading and DNA separation. The fabrication protocol was inspired by the print, cut and laminate (PCL) technique described previously by our group, and in accordance, offers a rapid and inexpensive option compared with existing approaches. The device comprises multiple polyester-toner fluidic layers, a cyclic olefin copolymer separation domain and integrated gold leaf electrodes. All materials are commercially-available and complement the PCL process in a way that permits fabrication of increasingly sought after single-use devices. All reagents, including a viscous sieving matrix, are loaded centrifugally, eliminating external pneumatic pumping, and the sample is separated in <5 minutes using an effective separation length of only 4 cm (reagent loading to completed separation, is <37 minutes). The protocol for gold leaf electrode manufacture yielded up to 30 electrodes for less than $3 (cost of a 79 mm × 79 mm gold leaf sheet) and when using a device combining these electrodes and centrifugal reagent/polymer loading, the electrophoretic separation of STR fragments with two base resolution was demonstrated. This exemplary performance makes the device an ideal candidate for further integration and development of an inexpensive, portable and rapid forensic human identification system.